Visual Merchandise Marketing Communication Camperia Café & Resto Payakumbuh Dengan Konsep Camping Ground - Febrian Daviel Mustafa; Heldi Heldi (SENIMAN: Jurnal Publikasi Desain Komunikasi Visual, 2023)
The business world requires companies to increase product renewal, including visual merchandising, to attract consumer visits to obtain company income. Visual merchandising in companies can make asset visualizations look more attractive. Visual merchandising will provide visualization of product placement to assist marketing at Camperia Café & Resto in order to have a comfortable, relaxed and quiet atmosphere to be enjoyed. The design objective is to apply the camping ground concept in miniature form to get a unique Camperia Cafe & Resto atmosphere in the eyes of the target audience. 4D design and analysis methods use AIDAS to produce relevant work. The design results are in the form of mockups with supporting media in the form of catalogs, animated videos, posters, x-banners, stickers, key chains, and mugs.